Interlinked personal story information and user interest in weblog by RSS, FOAF, and SIOC technology - binti Mohd Zulkefli, N.A. (Springer Verlag, 2014)
Interlinked Personal Story and user interest in Weblogs to re-use information in the blog contents is a new way of communication in a Weblog field. With many existing vocabularies such as Rich Site Summary (RSS), Friend of a friend (FOAF) and Semantically Interlinked Online Community (SIOC), interlinked among blogs can successfully help users especially bloggers to find the relationship that occurs inside the contents of the blogs itself. Furthermore, nowadays, personal blog contents are more useful to serve as the answer to the Internet usersâ search for information rather than existing search engines where personal blog contents are always updated. Our proposed framework system is designed to accomplish the motivation to interlink personal information weblogs and also to improve the uses of the blog among the online community. Â© 2014 Springer International Publishing Switzerland.